Muscle damage responses to resistance exercise performed with high-load versus low-load associated with partial blood flow restriction in young women - Fernanda Alvarez, I.; Damas, F.; Pires de Biazon, T. M.; Miquelini, M.; Doma, K.; Libardi, C. A. (European Journal of Sport Science, 2020)
The aim of this study was to compare if an acute exercise session of high-load resistance training (HL-RT, e.g. 70% of 1 repetition-maximum, 1 RM) induces a higher magnitude of muscle damage compared with a RT protocol with low-loads (e.g. 20% 1 RM) associated with partial blood flow restriction (LL-BFR), and investigate the recovery in the days after the protocols. We used an unilateral crossover research design in which 10 young women (22(2) y; 162(5) cm; 66(11) kg) performed HL-RT and LL-BFR in a randomized, counterbalanced manner with a minimum interval of 2 weeks between protocols. Indirect muscle damage markers were evaluated before and once a day for 4 days into recovery. Main results showed decreases of 8-12% at 24-48 h in maximal voluntary isometric and concentric contraction torques (P < 0.03), and changes in muscle architecture markers (P < 0.03) for HL-RT and LL-BFR, with no differences between protocols (P > 0.05). Moreover, delayed onset muscle soreness increased only after LL-BFR (P < 0.001). We conclude that an acute bout of low volume HL-RT or LL-BFR to failure resulted in edema-induced muscle swelling, but do not induce major or long-lasting decrements in muscle function and the level of soreness promoted from LL-BFR was mild.